2021
DOI: 10.1101/2021.03.20.21254005
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alternative splicing of OAS1 alters the risk for severe COVID-19

Abstract: A locus containing OAS1/2/3 has been identified as a risk locus for severe COVID-19 among Europeans ancestry individuals, with a protective haplotype of ∼75 kilobases derived from Neanderthals. Here, we show that among several potentially causal variants at this locus, a splice variant of OAS1 occurs in people of African ancestry independently of the Neanderthal haplotype and confers protection against COVID-19 of a magnitude similar to that seen in individuals without African ancestry.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…A different Neanderthal haplotype block, at the OAS1-OAS3 cluster, is protective against severe COVID-19 in Eurasians [117][118][119] , producing an OAS1 splice form with higher enzymatic activity 128 . The ancestral variant, still present in Africans, appears to confer a similar magnitude of protection against severe COVID-19, underscoring the value of the reintroduction 129 .…”
Section: The Continuous Evolution Of Immune Variationmentioning
confidence: 85%
“…A different Neanderthal haplotype block, at the OAS1-OAS3 cluster, is protective against severe COVID-19 in Eurasians [117][118][119] , producing an OAS1 splice form with higher enzymatic activity 128 . The ancestral variant, still present in Africans, appears to confer a similar magnitude of protection against severe COVID-19, underscoring the value of the reintroduction 129 .…”
Section: The Continuous Evolution Of Immune Variationmentioning
confidence: 85%
“…Our evaluation of OAS1 antiviral activity in vitro, combined with our analysis of OAS1 transcripts in patient cohorts, indicates that the protective Neanderthal OAS1 haplotype ( 22 , 24 ) likely prevents severe disease through specifying the expression of prenylated OAS1, which directs dsRNA sensing to the sites of SARS-CoV-2 replication. Indeed, through combining multiple studies, Huffman et al , also concluded that the Rs10774671 SNP is responsible for the protection conferred by the Neanderthal haplotype ( 59 ).…”
Section: Prenylated Oas1 Is Associated With Less Severe Covid-19mentioning
confidence: 99%
“…A study has shown that a major genetic risk factor for severe COVID-19 is linked to the Neanderthal genome 16 . A single point mutation in the OAS1 gene affecting splicing, and possibly OAS1 levels, has been identified [17][18][19] . To follow up on these studies, we investigated whether patients carrying this mutation had a different disease outcome and possibly a unique transcriptome signature.…”
Section: Longitudinal Analysis Of the Immune Transcriptomes While Hos...mentioning
confidence: 99%